A THESIS IN THE DEPARTMENT OF BOTANY SUBMITTED TO THE FACULTY OF SCIENCE IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE AWARD OF DEGREE OF DOCTOR OF PHILOSOPHY OF UNIVERSITY OF IBADAN (2016)
Macrophytes such as Eichhornia crassipes and Pistia stratiotes are known bioaccumulators found in the Ologe Lagoon which receives effluents mainly from Agbara Industrial Estate. However, the mechanism of heavy metal bioaccumulation by these macrophytes has not been fully understood. This study was designed to determine the mechanism of heavy metal bioaccumulation and model the phytoremediation capabilities of the macrophytes. Five sampling stations: Owo (before the point of discharge of effluent as control), Agbara, Otto Jetty, Morogbo and Etegbin (after the point of effluent discharge) were selected for the study. Water samples, sediments, E. crassipes and P. stratiotes were collected using standard procedures in these stations from July, 2013 to December, 2014 from the lagoon and analysed for heavy metals using standard methods. Temperature, pH, Conductivity, Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Dissolved Oxygen (DO) were determined according to APHA methods. Selected heavy metals: Zn, Fe, Cu, Pb and Cd in water, sediments and the two macrophytes were determined in accordance with FAO/SIDA method. Eichhornia crassipes and P. stratiotes were grown in three different concentrations (10, 15 and 20 mg/L) of CuSO4.5H2O; ZnSO4; FeSO4.7H2O and Pb(NO3)2 in three replicates for six weeks. Thereafter, plant leaves, stems and roots were harvested and analysed for metal bioaccumulation and translocation. Time evolution of pollution was determined using first and second-order kinetic models. Data were analysed using descriptive statistics, ANOVA and Fisher’s LSD test (α0.05). Water temperature ranged from 28.7±0.37-29.4±0.69°C, pH (6.7±0.1-6.9±0.1), Conductivity (1565±784.7-3088±1478.6 μS/cm), TSS (10.4±0.5-20.6±1.2 mg/L), TDS (89.2±1.8-1739±872.2 mg/L), BOD (2.9±0.7-3.7±0.2 mg/L), COD (13.8±0.8-23.9±1.0 mg/L) and DO (4.2±0.2-4.9±0.2 mg/L). UNIVERSITY OF I BADAN LIBRARY vi The concentration of Zn (30±2.0 μg/L) in water sample was higher than the USEPA limit (6 μg/L at 45 mg/L hardness) for the protection of aquatic ecosystems. The highest {Fe (2310±613 mg/kg) and Cu (38.20±10.21 mg/kg)} and lowest {Fe (1305±848 mg/kg) and Cu (2.92±0.37 mg/kg)} concentrations in sediment were recorded in Agbara and Etegbin respectively. The concentration (mg/kg) of heavy metals in E. crassipes and P. stratiotes from Agbara was significantly higher (Fe=1368±236.12; Zn=42.60±5.62) than values obtained from other sampling stations (Fe=470±55.96-642.58±303.26; Zn=11.14±1.83-20.41±4.31). In the laboratory experiment, metals were accumulated through the roots to the shoot (phytoextraction) via a concentration gradient (for E. crassipes pots spiked with 10, 15 and 20 mg/L of Zn, the average quantity of the metal absorbed were 5.56±0.09, 8.89±0.60 and 15.58±0.15 mg/L respectively). The bioaccumulation factor in E. crassipes varied from 10 (Pb) to 9000 (Fe) while in P. stratiotes, it varied from 9 (Pb) to 8500 (Cu). Translocation factors were higher in root/stem (7.06±1.09 for Pb) than stem/leaf (5.42±1.12 for Pb). Iron accumulation in different parts of E. crassipes {(mg/kg) was: {leaf (0.45±0.06-15.58±0.15); stem (0.33±0.05-16.48±0.44); root (0.40±0.07-18.50±3.16)} and P. stratiotes was: {leaf (0.36±0.06-6.67±1.17) and root (0.45±0.08-7.49±1.78)}. Pots seeded with Fe maintained green colouration for a longer time than those seeded with Cu, Zn and Pb. The time evolution of pollution was best described by first-order kinetic model. Eichhornia crassipes and Pistia stratiotes bioaccumulated heavy metals and the mechanism of bioaccumulation is a function of time and level of concentration of the heavy metals. Keywords: Bioconcentration factors, Translocation factors, First-order kinetic model Word count: 498